Health care finance, economics, and policy for nurses : a foundational guide - Rambur, Betty (Springer Publishing Company, 2015)
The complexities of health care finance, economics, and policy are today inextricably intertwined with traditional nursing practice. This undergraduate nursing text distills these challenging topics into an engaging, easy-to-read format that facilitates ready application into any practice setting.